Rationality and Mechanism. A Reading of Statesman and Laws X - Santa Cruz, María Isabel (Estudios de Filosofía, 2002)
In Statesman (268d-277); the fiction story of the periodical reversion of the universe expresses the existence of two forces in the universe or two tendencies of occurrence. One that guides the world and man towards his télos, which is the most perfect, and the tendency towards disorder and confusion, in other words, just mechanical and risky. Purpose and mechanism, the two tendencies present in Timaeus, reappear in book X of Laws under the form of a good soul and a bad soul. The former is the one that recounts the rational movement of the world and the latter is the causer of the mad and irregular movement (897c-d). In Statesman, the tendencies, or ruling forces of the universe, alternate their predominance, they are in tension. In addition, it is the measure of that alternation, which saves the worldfrom destruction and it makes it stay- balanced. This game of tensions translates the existence of a proportionality in the heart of the universe: thanks to which the world is precisely a Kósmos. In Timaeus, balance results from the persuasion that intelligence exerts on necessity, guiding it towards the best. This idea also reappears in Laws; in 906a: this balance consists on a tension between that which is rational and that which is irrational in the universe.